Kinematics and mechanism of rigid-flex elastic screening for moist coal under disequilibrium excitation. Issue 6 (3rd June 2022) - Jiang, Haishen; Yu, Shijie; Huang, Long; Zhao, Yuemin; Duan, Chenlong; Wang, Quanqiang; Luo, Zhenfu; Liu, Chusheng; Zhou, Zhiguo; He, Jingfeng; Tang, Ligang; Cao, Xiaoqiang
ABSTRACT: Elastic screening methods are widely used in the classification of moist coal as they can overcome the problem of aperture blockage. However, the use of an equally inclined screen surface with balanced excitation facilitates material accumulation, worsening the screening performance. Here, a disequilibrium excitation structure was proposed to solve the accumulation problem, and its synchronization process was studied using a high-speed camera system. The spatial motion of the rigid-flex elastic screen surface along material flow direction was reconstructed using a vibration test system. The influence of disequilibrium excitation force coefficient ( F de ) and relative vibration motor shaft span ( l vms ) on the screening performance of moist coal was investigated. The results showed that the phase difference between the two eccentric rotors gradually decreased to 0 under the coupling effect of the electromechanical system, achieving synchronous stable operation. The spatial trajectories of different parts of the rigid-flex elastic screen surface were close to ellipsoidal, with the long axis of the ellipse decreasing along the direction of material flow. The screening efficiency showed a maximum and the total misplaced materials showed a minimum with increasing F de and l vms . The optimum screening efficiency of 86.35% and the corresponding total misplaced materials of 5.03% were achieved at F de = 1.15 and l vms = 40%. Compared to the equilibrium excitation structure, the elastic screening process was enhanced by the use of disequilibrium excitation, with the screening efficiency increasing by 3.20%.